UV Spectrophotometric Determination of Some Anti-HIV Drugs - Sankar, D.G.; Reddy, M.V.V.N.; Rajendra Kumar, J.M.; Murthy, T.K. (Asian Journal of Chemistry, 2010)
A simple and sensitive UV spectrophotometric method for the determination of four anti-HIV drugs, lamivudine, stavudine, nelfinavir mesylate and nevirapine was developed with λmax 270 nm, 265 nm, 253 nm and 284 nm respectively and these methods are extended to pharmaceutical preparations. There is no interference from any common pharmaceutical additives and diluents.